Genotyping of Acanthamoeba spp. from Soil in Narathiwat Province, Thailand - Hounkong, Kruawan; Sornying, Peerapon; Buatong, Jirayu; Sawangjaroen, Nongyao (Princess of Naradhiwas University Journal, 2022)
Acanthamoeba spp. are free-living amoeba which are widely distributed worldwide. Some genotypes are known to cause diseases in corneal and central nervous system. In the present study, Acanthamoeba spp. (44 isolates) obtained by culture and identify under microscope from soil in 3 districts (Bacho, Yi-ngo, and Ra-ngae) of Narathiwat province from our earlier survey were used. The identification and genotyping of Acanthamoeba spp. were performed by PCR reactions and DNA sequencing. The results showed that 34.1% (15/44) were positive for Acanthamoeba spp. and belong to genotypes T3 (3 isolates), T4 (5 isolates), T5 (4 isolates), T17 (1 isolate) and T18 (2 isolates). Genotypes T3, T4, T5 and T18 have been reported to associate with human diseases. This is the first report proving the contamination of pathogenic Acanthamoeba spp. in soil from Narathiwat province.